Synthesis, characterization and photocatalytic properties of nanostructured lanthanide doped β-NaYF4/TiO2 composite films - Pennisi, Fabiana M.; Pellegrino, Anna L.; Licciardello, Nadia; Mezzalira, Claudia; Sgarzi, Massimo; Speghini, Adolfo; Malandrino, Graziella; Cuniberti, Gianaurelio (Giovanni) (Scientific Reports, 2022)
The photocatalytic approach is known to be one of the most promising advanced oxidation processes for the tertiary treatment of polluted water. In this paper, β-NaYF4/TiO2 composite films have been synthetized through a novel sol–gel/spin-coating approach using a mixture of β-diketonate complexes of Na and Y, and Yb3+, Tm3+, Gd3+, Eu3+ as doping ions, together with the TiO2 P25 nanoparticles. The herein pioneering approach represents an easy, straightforward and industrially appealing method for the fabrication of doped β-NaYF4/TiO2 composites. The effect of the doped β-NaYF4 phase on the photocatalytic activity of TiO2 for the degradation of methylene blue (MB) has been deeply investigated. In particular, the upconverting TiO2/β-NaYF4: 20%Yb, 2% Gd, x% Tm (x = 0.5 and 1%) and the downshifting TiO2/β-NaYF4: 10% Eu composite films have been tested on MB degradation both under UV and visible light irradiation. An improvement up to 42.4% in the degradation of MB has been observed for the TiO2/β-NaYF4: 10% Eu system after 240 min of UV irradiation.
CRIS-Team Scopus Importer:2023-03-20